Bibliometric Analysis of Integrating Blue Curriculum with Technology: A Sustainable Approach to Education - Muktiarni, M; Widiaty, Isma; Rahayu, Nur Indri; Al Husaeni, Dwi Fitria; Ismail, Affero (Universitas Komputer Indonesia, 2023)
This study aims to investigate the global research landscape on integrating Blue Curriculum with technology to promote sustainable education. The study uses bibliometric analysis methods with the help of VOSviewer and RStudio applications. By analyzing publications from 2000 to 2024 sourced from the Scopus and Web of Science database, the study identifies trends, influential authors, institutions, and research hotspots. The results show a steady growth in research output, with significant contributions from journals such as Sustainability, Marine Policy, and Environmental Education Research. Keyword co-occurrence analysis highlights clusters related to the blue economy, technology integration, and interdisciplinary approaches, reflecting strong alignment with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 14 (Life Below Water). The findings reveal increasing international collaboration and highlight emerging themes such as gamification, virtual reality, and AI-based learning tools in ocean literacy. However, challenges such as the digital divide and limited access to resources in certain regions remain. This study provides recommendations for local curriculum development, long-term impact studies, and interdisciplinary research to address these challenges and enhance technology integration in sustainability education. This analysis provides a roadmap for future research and underscores the potential of the Blue Curriculum to reshape global education for sustainability.